Low-temperature plasma radiofrequency ablation in phantom limb pain: A case report - Hongyan Li; Yan Li; Zhaoxuan Guo; Liyan Hao; Yinyin Li; Yuanzhang Tang; Yuna Guo; Daqian Zhang; Liangliang He; Yan Wang; Yuanguang Meng; Fei Li; et al. (Brain Circulation, 2018)
Phantom limb pain (PLP) and phantom limb sensations are common complications postamputation. PLP is defined as persistent painful sensations perceived in the missing portion of the amputated limb. Low-temperature plasma radiofrequency ablation (coblation) technology is a relatively new technology that has shown promise in treating neuropathic pain. This report illustrates the use of coblation technology on cervical nerve roots for PLP. Coblation of the cervical nerve root was performed. Three 17G puncture trocars were placed near the C5–C6, C6–C7, and C7–T1 intervertebral foramen with computed tomography (CT) guidance. Then, a coblation needle attached to low-temperature plasma multifunctional operation system was placed near the C8 nerve root through the puncture trocars. To locate the target nerve, single stimulation (lasting for 5 s, at 1 intensity) in “cut” and “coagulation” model was given to serve as a sensory stimulation test. The stimulation induced radiating pain of the stimulated nerve away from the stimulation site to confirm our target nerve. The needle location was redirected based on the reproduction of the patient's symptoms with minimal intensity. A CT-guided cervical nerve root coblation was performed to obtain longer PLP relief. The patient reported pain relief in PLP after the operation. At 1-, 3-, and 6-month postoperative review, PLP relief was achieved. Overall activity was improved and there was necessarily need for pain medications. However, the doses of medicine significantly decreased. The analgesic effect was stable during the 6-month follow-up period. Our report demonstrates that coblation technology is successful treatment for PLP in this case. It will supply us a novel navigation in PLP treatments. Meanwhile, this finding still needs additional study for confirmation.